Cutaneous clear cell/signet-ring cell squamous cell carcinoma arising in the right thigh of a patient with type 2 diabetes: combined morphologic, immunohistochemical, and etiologic analysis. Issue 1 (December 2016) - Wang, Nong-Rong; Wang, Meng-Meng; Zhou, Lv; Liu, Ze-Lin; Chen, Nan-Ping; Hu, Jin-Ping; Deng, Yan-Juan; Qi, Xiao-Qing; Huang, Xiao-Feng; Su, Yue; Zhang, Si-Yao; Tong, Fei; et al.
Abstract Background The clear cell/signet-ring cell variant of cutaneous squamous cell carcinoma (cSCC) is extremely rare. Its carcinogenesis has consistently been linked to ultraviolet radiation and HPV in the literature. However, there is little definite information about the contribution of diabetes mellitus (DM) to cSCC. Case presentation A 78-year-old Chinese woman with type 2 DM presented with a mushroom-like lump in her right thigh. Histological findings revealed that the lesion was mainly composed of clear cells and signet-ring cells. The septa of vacuoles in cytoplasm displayed positivity for periodic acid schiff (PAS) and cytokeratins such as AE1/AE3, CK5/6, CK14, and CK19. Malignant cells did not express CK7, CK8, CK18, CK20, p16, p53, or c-erbB-2, and the Ki-67 index was less than 5 %. We further explored the etiology of clear cell/signet-ring cell cSCC using human papillomavirus (HPV) type-specific PCR and genotyping and confirmed that the patient was not infected with HPV. Nucleus positivity for p63 indicated the involvement of the p53 family in the lesion. Meanwhile, the expression of fibroblast growth factor receptor-2 (FGFR2), a downstream effector of p63, was upregulated in tumor cells. Conclusions This study provides the first report on the clear cell/signet-ring cell variant of cSCC found in the right thigh of a patient with type 2 DM. Metabolic imbalance in addition to conventional pathogens such as UV and HPV may contribute to the development of the lesion via p63/FGFR2 axis.